Recent advances in systemic therapy for hepatocellular carcinoma - Huajun Zhang; Wuyang Zhang; Longying Jiang; Yongheng Chen (BMC, 2022)
Abstract Hepatocellular carcinoma (HCC) is one of the most common and lethal malignant tumors in the world. Therapeutic options for advanced HCC are limited. Systemic treatment, especially with conventional cytotoxic drugs, is usually ineffective. For more than a decade, sorafenib has been the only systemic drug that has been proven to be clinically effective for treating advanced HCC. However, over the past three years, the rapid progress of molecular targeted therapies has dramatically changed the treatment landscape for advanced HCC. Immune checkpoint therapies are now being incorporated into HCC therapies, and their combination with molecular targeted therapy is emerging as a tool to enhance the immune response. In this review, we summarize the development and progress of molecular targeted agents and immunotherapies in HCC.